Serum leptin levels in obsessive-compulsive disorder - Atmaca, M; Tezcan, E; Kuloglu, M; Ustundag, B (Wiley, 2005)
The aim of the present study was to evaluate serum leptin levels to demonstrate whether or not its eventual alterations might have an etiopathogenetic significance in patients with obsessive-compulsive disorder (OCD). Thus, it was planned to examine whether serum leptin levels were affected by pure OCD (OCD-D), pure depression (D) or the comorbidity of OCD and depression (OCD+D). Forty-four patients with OCD (27 with OCD-D and 17 with OCD+D), 38 depressed patients and 30 control subjects were enrolled and serum leptin and cortisol levels were measured. According to the mean leptin levels, no significant difference was found between the OCD-D and control groups and between the OCD+D and D groups, while statistically significantly lower levels were found in the OCD+D and D groups than in control group. Significant difference in the mean leptin levels was found among groups even after controlling for body mass index or sex. The present study confirms the strong relationship between serum leptin and cortisol values and suggests that reduced leptin levels, rather than having an etiopathogenetic significance in patients with OCD, seem to be associated with patients with OCD and depression but not with pure OCD patients, and that OCD may be a heterogeneous subtype containing some biological indications of anxiety and affective disorders.
Keywords: cortisol; depression; leptin; OCD